Economic development in China, India and East Asia managing change in the twenty first century - Roy, Kartik Chandra 1941- (Edward Elgar E-Book Archive, 2012)
1. Evolution of the developmental state -- 2. Institutional foundations of a developmental state -- 3. Institutional foundations of East Asian and South Asian states -- 4. Trade, technology and industrialization in the Asian states -- 5. Growth and income distribution in the Asian states -- 6. Poverty and human development in the Asian states -- 7. Managing development in the Asian states -- 8. Should political openness precede economic openness? The Asian experience -- 9. Development and institutions in Asia : pertinent lessons